STUDENTS' PERCEPTIONS ON THEIR READINESS TO STUDY ONLINE: A CASE STUDY OF ONE UNIVERSITY IN SURABAYA - Zainul Aminin; Ayunita Leliana (IKIP Siliwangi, 2021)
The purpose of this study was to explore students' activities and perceptions in carrying out online lectures through the WhatsApp Group application, Google Classroom, and Zoom and finding effective ways to study during the COVID-19 outbreak. This study was expected to identify the readiness of students to follow online lectures and find effective ways to study as well as being the basis for higher education institutions to establish policies for implementing online lectures. The researcher used a qualitative study. The participants were the 33 EFL students of the English Department both male and female who joined the Essential Writing Class. The researcher used convenience sampling which invited subjects to participate. The instruments used in this research were a questionnaire and a semi-structured interview. Data analysis used was thematic coding. The results show that most students were ready to study online. They only focused on the material. However, they did not pay attention to the way they learned; that was online learning. There are three aspects involved to make the class more effective; they are the lecturer, the students, and the media. These three aspects must work together to create effective online courses. Keywords: perception, readiness, online